Advancing Digital and Technology Literacy through Qualitative Studies to Bridging the Skills Gap in the Digital Age - Junaedi, Achmad Tavip; Panjaitan, Harry Patuan; Yovita, Indri; Veronica, Kristy; Renaldo, Nicholas; Jahrizal, Jahrizal (Journal of Applied Business and Technology, 2024)
The digital age has transformed the way individuals live, work, and interact, with innovations like artificial intelligence, cloud computing, and the Internet of Things (IoT) reshaping industries and societies. This study examines the key obstacles to improving digital and technology literacy and proposes strategies to bridge this gap. The research focuses on developing economies, where socio-economic, infrastructural, and educational barriers exacerbate the digital divide. Employing a qualitative literature review, the study analyzes peer-reviewed articles, reports, and case studies to identify the main challenges and successful interventions in promoting digital literacy. The novelty of this research lies in its contextual focus on developing economies, its multi-sectoral approach involving public and private collaboration, and its emphasis on tailored, lifelong learning programs. By integrating case studies and a thematic analysis of current initiatives, this study provides actionable recommendations for advancing digital and technology literacy, enabling individuals and organizations to fully participate in an increasingly digital world. Advancing digital and technology literacy is vital for closing the skills gap in today’s digital age. Despite numerous initiatives, challenges such as limited access, resistance to change, and inadequate educational programs persist. Holistic, multi-sectoral approaches are necessary to create meaningful improvements in literacy rates, contributing to social mobility and economic development. Future studies could use a quantitative approach to measure the impact of specific interventions on digital literacy. Longitudinal research could track the effectiveness of ongoing programs in different socioeconomic settings.